PENGEMBANGAN E-MODUL BERBANTUAN FLIPBOOK KEANEKARAGAMAN MANGROVE BERBASIS RISET DI TELAGA WASTI PADA MATA KULIAH KEANEKARAGAMAN TUMBUHAN - Nebore, Idola Dian Yoku; Anita, Agustina; Erari, Semuel Sander; Iwan, Iwan; Rumalolas, Nuryanti; Tuririday, Helena Trivona (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Students often face challenges in understanding botanical terms, which hinders their comprehension of plant diversity topics. Additionally, the lack of available e-modules has led students to rely heavily on internet sources, making the learning process less effective. This study aims to develop contextual e-modules focused on mangrove plants in Telaga Wasti as supplementary teaching materials for plant diversity courses. The research follows a Research and Development (R & D) approach, employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to guide the creation of the e-modules. The research instruments consist of media and material expert validation sheets, student response questionnaire sheets, lecturer interview sheets, and pretest and posttest questions. The study evaluates the e-modules in terms of validity, practicality, and effectiveness. Validation by expert reviewers resulted in a score of 90,32%, categorized as "very valid." A student response questionnaire indicated a 91,1% positive response, classifying the modules as "very practical and effective." Post-test results showed an average score of 71,87, The average N-Gain value is 0,56 (0,30 â‰¤ N-Gain < 0,70) with the criteria of being moderate or quite effective in improving learning outcomes. In conclusion, the contextual e-modules on mangrove diversity in Telaga Wasti are considered suitable for use in plant diversity courses, the criteria of being valid, practical, and moderate effective for higher education learning environments. Keywords: Development, E-Modul, Mangrove, Diversity